Use of psychocorrectional techniques for restoring mental activity in patients after severe traumatic brain injury at the stage of confusion syndromes - O. V. Kulyk; W. Zukow (Kazimierz Wielki University, 2017)
The work is based on the results of diagnosis, rehabilitation and restorative treatment of 220 patients with post-coma long-term consciousness disorders after severe traumatic brain injury. The main attention is paid to the actual topic of the restoration of mental activity at the stage of confusion in line with the stages of classification according to Dobrokhotova T. A. in the course of the rehabilitation route. This is the use of psychocorrectional techniques for restoring mental activity in patients after severe traumatic brain injury at each of the stages (6A, 6B, 6C). The research reveals that, although patients within their groups at the stages 6A, 6B, 6C had almost identical (with individual fluctuations) physical capabilities, social skills, similar in their main features neurological status, but differed in the results of the restoration of mental (intellectual mnestic) functions. During the gradual transition of patients from stage to stage of syndromes of consciousness reintegration, tasks and techniques were introduced aimed at improving speech and higher cortical functions through which the social activity of patients grew. For the first time it was recorded that the restoration of mental activity occurred faster than obtaining some new kinetic or locomotor skills. The study emphasizes that the combination of techniques connected to the rehabilitation program at the time of the stages migration, from confusion with aspontaneity to speech-motor confusion and, subsequently, amnestic confusion was of great prognostic value. At the same time, there was no clear correlation between the restoration of mental functions and motor activity, since the reintegration of consciousness occurred with individual characteristics and reactive perception of the influence of kinesiological methods by each patient. Dependence of family history, behavioral reactions, characteristic features and accentuations of the individual, emotional-volitional reserve and reactivity, intellectual abilities, cognitive potential, the level of differentiation of personality to trauma on the speed and quality of recovery of consciousness was found. On the basis of the obtained data, the conclusion is made about the importance of using adequate psychopharmacocorrection at each of the stages of consciousness recovery depending on the clinical manifestations, the main syndromes and the dynamics of psycho-emotional reactions. The most significant results were received by application of medicines from the group of antidepressants (selective serotonin reuptake inhibitors (SSRIs) and medicines with antipsychotic (neuroleptic) influence for smoothing of polar manifestations and pathological psychotic reactions. The importance of psychocorrectional techniques selection and their combinations at each link in the chain of consciousness recovery was revealed. And the dynamics of changes indicated the reserves of the higher mental processes of each patient.